Rheumatoid Arthritis and Mortality in End Stage Renal Disease. Issue 2 (March 2020) - Paudyal, Sunita; Waller, Jennifer L.; Oliver, Alyce; Le, Brian; Zleik, Nour; Nahman, N. Stanley; Carbone, Laura
Abstract : Objective: To determine whether rheumatoid arthritis (RA) is a risk factor for cardiovascular disease (CVD) events, all-cause mortality and cardiovascular mortality in End Stage Renal Disease (ESRD). Methods: Cohort study of adult patients with ESRD in the United States Renal Data System (USRDS) with RA and a 5% random sample of those without RA. CVD events, all-cause mortality and cardiovascular mortality were determined in those with RA compared to those without RA using Cox Proportional Hazards modeling. Results: 2, 824 subjects, 407 with RA and 2, 417 without RA, were included in the analyses. The duration of the study was up to 5 years, depending on mortality and initiation of dialysis. There were no significant differences in CVD events by RA status (n = 311 [76.4% RA] vs. n = 1936 [80.1% without RA], p = 0.09). Subjects with RA had a significantly shorter mean time in months from start of dialysis to an incident CVD event (20.1 ± 12.2 vs. 21.2 ± 14.1, p < 0.01) than those without RA. In multivariable adjusted models, RA was not associated with an increased risk for all-cause mortality (aHR = 1.09, 95%CI 0.94–1.27) or cardiovascular mortality (aHR = 0.95, 95% CI 0.74–1.22) within 5 years. Risk factors for all-cause mortality and cardiovascular mortality in RA included older age and a higher Charlson comorbidity index (CCI). Conclusions: Clinicians should be aware that persons with RA who develop ESRD incur cardiac events sooner than the general population. However, RA is not an independent risk factor for all-cause or cardiovascular mortality in ESRD.